The Impact of the Educational Program Using Teaching Aids in Teaching the Skills of Service Receiving and Court Defending for the Students the Volleyball - Majid Hameed Merzah (Journal of Global Pharma Technology, 2018)
The coaches and experts interested in preparing the volleyball teams from the physical, skill, planning and psychological aspects of their teams, on a set of bases, the most important of which are the basic skills which vary in level of complexity and complexity from one game to another .Based on this sense of importance of these skills, which reduces efforts, shortens time and material possibilities, and makes early learning processes a little more erroneous because errors at these stages, if developed, are difficult to correct. And through the researcher's practice of this game found that these skills are still taught in traditional ways, and educational curricula in the general sphere of volleyball lacks the use of aids and devices that help to accelerate and stabilize the processes of education and consolidate the differences between these skills, the use of traditional methods of learning, which It is not possible to arrive at a precise description or measurement of learning, and non-objective evaluation is accompanied by many errors in accurate monitoring of the movement parts.The Research ObjectsFind educational aids to teach students the skills of service receiving and paying volleyball students.Learning about the impact of the learning program using some educational aids in teaching the skills of service receiving and paying students with volleyball.The researchers used the experimental method in the style of equal groups to suit the problem. The research society determines the students of the second stage in the Faculty of Physical Education and Sports Sciences at the University of Karbala for the academic year 2016-2017 Division (A, B, C) and the number of (82) (24) students, divided into two groups of each group (12) students.The Most Important Conclusions WereThe proposed learning program using innovative teaching methods has a positive impact on teaching service receiving skills.The proposed learning program using innovative teaching aids has a positive impact on the teaching of court defending skill.Keywords: Educational program, Teaching aids, Receiver service and defending of pitch skills.